2013
DOI: 10.1037/a0032809
|View full text |Cite
|
Sign up to set email alerts
|

Joint influences of individual and work unit abusive supervision on ethical intentions and behaviors: A moderated mediation model.

Abstract: We develop and test a model based on social cognitive theory (Bandura, 1991) that links abusive supervision to followers' ethical intentions and behaviors. Results from a sample of 2,572 military members show that abusive supervision was negatively related to followers' moral courage and their identification with the organization's core values. In addition, work unit contexts with varying degrees of abusive supervision, reflected by the average level of abusive supervision reported by unit members, moderated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 69 publications
9
123
1
Order By: Relevance
“…Moreover, in contrast to the focus on value identification and the emphasis on the role of leaders in conveying organizational values to employees examined in Hannah et al's (2013) study, our research focuses on an identification mechanism that involves not only a cognitive component (e.g., value identification), but also the evaluative and affective components. Although organizational identification was also examined by Loh et al (2010), we extend their work by providing a thorough examination on the boundary conditions of workplace aggression in influencing organizational identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in contrast to the focus on value identification and the emphasis on the role of leaders in conveying organizational values to employees examined in Hannah et al's (2013) study, our research focuses on an identification mechanism that involves not only a cognitive component (e.g., value identification), but also the evaluative and affective components. Although organizational identification was also examined by Loh et al (2010), we extend their work by providing a thorough examination on the boundary conditions of workplace aggression in influencing organizational identification.…”
Section: Discussionmentioning
confidence: 99%
“…As such, another research approach to workplace aggression is to establish a theoretical framework to capture the commonality of different forms of workplace aggression and explain its consequences on employee outcomes (e.g., Aquino & Thau, 2009;Hershcovis, 2011;Smart Richman & Leary, 2009;Spector & Fox, 2005). Based on findings in previous studies (Hannah et al, 2013;Loh et al, 2010) and our research, an identification perspective based on social identity theory can offer a theoretical foundation to explain the commonality of different forms of workplace aggression (e.g., abusive supervision, workplace bullying, and workplace ostracism) in influencing employee outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hannah et al (2013) found that moral courage mediated the relationship between abusive supervision and unethical behavior. Specifically, Hannah and colleagues argued that abusive supervision has a negative effect on followers' moral courage which, in turn, can lead to the mistreatment of individuals and other unethical behaviors such as lying, cheating, and stealing.…”
Section: Moral Courage As a Mediatormentioning
confidence: 99%
“…Although researchers have already established the relationship between abusive supervision and deviant workplace behaviors, the possible mediating effect of moral courage and the boundary conditions of these relationships have only begun to be explored. For example, using a military sample, Hannah et al (2013) found evidence of the mediating effect of moral courage on the relationship between abusive supervision and unethical behaviors (i.e., mistreatment on non-combatants and intentions of reporting unethical behaviors). Their research called for examining the relationships between abusive supervision, moral courage, and unethical/deviant behaviors in non-military samples.…”
Section: Deviant Workplace Behaviorsmentioning
confidence: 99%